Men's stories : an analysis of men's talk of separation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Psychology, Massey University, Palmerston North, New Zealand, 2006 - Kendall, Ross D (Massey University, 2006)
This study, examining men's talk about separating from relationships, uses a hybrid model of discourse and structural analysis. The research identifies four dominant discourses: a legal system discourse, a discourse of morality, a discourse of masculinity and a discourse of journeying. The men construct their experiences as negative occurrences: destructive and painful; but also as positive events: necessary, timely and ultimately beneficial. Their use of the discourses serves two opposing purposes: to position them as relatively innocent and vulnerable in the breakdown of their relationships, and as resolute, determined and in control of their lives. The dialectical clash of these themes leads in most cases to a position where the men can act as moral agents with clear aims and goals.
Keywords: Separation (Law) -- Psychological aspects; Divorced men -- Psychology